TOE? --> E(n) = f^(1+(n-3)) * c^(2+(n-3)) TOE --> E(n) = f^(1+(n-3)) * c^(2+(n-3)) Here's a possible TOE(Theory Of Everything). In order to show how the equation was derived, lets look at mass and how it relates to time in Einstein's Relativity equations; Mass In Relativity m = 1/(1-(v^2/c^2))^.5 Time in Relativity t = (1-(v^2/c^2))^.5 Mass is a result of the inversion of Time at any speed below "c" if (1-(v^2/c^2))^.5 in the equation; m = 1/(1-(v^2/c^2))^.5 is replaced with "t" Mass = 1/t The answer for Mass derived from the Relativity equations is similar to the answer of another equation; Frequency = 1/t Therefore; f = m = 1/t Freqency = Mass Which shows mass is a frequency; i.e. a vibration. The concept of wavelength is also connected to Frequency = Mass; Frequency = Wavelength/Time Frequency = Mass Mass = Wavelength/Time f = m = wavelength/time Both of the Frequency and Wavelength connections to Mass reveals the superstring theory where all subatomic particles in the Universe are made up of superstrings vibrating at different frequencies with different wavelengths. Now that we know Frequency = Mass, let's put it into E=mc^2; E = fc^2 All forms of energy, including light energy are basically vibrations at different frequencies. Charles Hinton, as well as Bernard Reimann, said light is a vibration of an unseen 4th Dimension. Since light photons are a form of electromagnetic energy, it's logical to conclude the entire electromagnetic spectrum from heat to gamma rays are vibrations in 3-Dimensional space caused by the 4th Dimension. Since all subatomic particles are made up of superstrings of energy that vibrate at particular frequencies, the vibration of the superstrings would logically be vibrations in 3-Dimensional space caused by the 4th Dimension. By logically extending this thought to other dimensions, it would mean that energy and matter in each dimension manifests from vibrations at particular frequencies which are caused by the next higher dimension. If the equation; E = fc^2 works for the 3rd Dimension, then we'd have to modify the equation so it works for all dimensions. By placing (n-3) in the exponents of the variables and use (n) to represent a dimension, we could make an equation that could work in any dimension; E(n) = f^(1+(n-3)) * c^(2+(n-3)) Dimension Zero E0 = f^-2 * c^-1 1st Dimension E1 = f^-1 * c^0 2nd Dimension E2 = f^0 * c^1 3rd Dimension E3 = f^1 * c^2 4th Dimension E4 = f^2 * c^3 5th Dimension E5 = f^3 * c^4 6th Dimension E6 = f^4 * c^5 7th Dimension E7 = f^5 * c^6 8th Dimension E8 = f^6 * c^7 9th Dimension E9 = f^7 * c^8 10th Dimension E10 = f^8 * c^9 The equation; E(n) = f^(1+(n-3)) * c^(1+(n-3)) Could be a possible candidate for TOE.